An Arabidopsis Prolyl 4 Hydroxylase Is Involved in the Low Oxygen Response - Konkina, Anna; Klepadlo, Mariola; Lakehal, Abdellah; Zein, Zein El; Krokida, Afroditi; Botros, Mina; Iakovidis, Michail; Chernobavskiy, Pavel; Elfatih Zerroumda, Mohamed; Tsanakas, George; Petrakis, Nikos; Dourou, Athanasia-Maria; et al. (Frontiers in Plant Science, 2021)
Plant responses to flooding, submergence and waterlogging are important for adaptation to climate change environments. Therefore, the characterization of the molecular mechanisms activated under hypoxic and anoxic conditions might lead to low oxygen resilient crops. Although in mammalian systems prolyl 4 hydroxylases (P4Hs) are involved in the oxygen sensing pathway, their role in plants under low oxygen has not been extensively investigated. In this report, an Arabidopsis AtP4H3 T-DNA knock out mutant line showed higher sensitivity to anoxic treatment possibly due to lower induction of the fermentation pathway genes, ADH and PDC1, and of sucrose synthases, SUS1 and SUS4. This sensitivity to anoxia was accompanied by lower protein levels of AGP-bound epitopes in the mutant line and induction of extensins-bound epitopes, while the expression levels of the majority of the AGPs genes were stable throughout a low oxygen time course. The lower AGPs content might be related to altered frequency of proline hydroxylation occurrence in the p4h3 line. These results indicate active involvement of proline hydroxylation, a post-translational modification, to low oxygen response in Arabidopsis.